A method for preparing and using a carbon fiber reinforced composite material having biological activity
Patent Information
- Application Number
- CN202410046925.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-12
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-01-12
AI Technical Summary
这极大地限制了它们的临床转化
[0026]1. The bioactive carbon fiber reinforced composite material obtained by this invention innovatively introduces DNA into medical bone repair materials. By responding to various external stimuli (pH, voltage), the DNA helical structure can be switched, thereby regulating surface properties such as surface wettability and zeta potential. It is an advanced material for bone engineering applications.
Smart Images

Figure CN117860960B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of biomedical materials technology, and in particular relates to a method for preparing and applying a bioactive carbon fiber reinforced composite material. Background Technology
[0002] Polyetheretherketone (PEEK) is a semi-crystalline synthetic polymer used in the manufacture of orthopedic implants. PEEK's excellent mechanical properties and resistance to degradation make it a promising alternative to metal and ceramic orthopedic implants. In particular, PEEK has a stiffness close to that of natural bone, which helps prevent stress shielding commonly found around harder implants made of metals such as titanium (Ti) and stainless steel. Furthermore, PEEK is ductile, making it easier to process than ceramic materials. Additionally, due to its chemical resistance, PEEK does not release toxic byproducts like metal implants when biocorrosion occurs. PEEK is also a radiolucent material, meaning it does not produce artifacts in X-ray and MRI images.
[0003] However, the inherent bioinertness and smooth surface properties of PEEK are detrimental to osteogenic differentiation. Furthermore, PEEK and CFRPEEK (carbon fiber reinforced polyetheretherketone) implants do not anchor to the surrounding bone through a process called osseointegration, but rather tend to be encapsulated by fibrous tissue and / or colonized by bacteria due to post-implantation foreign body reactions. This significantly limits their clinical translation. To overcome the bioinertness and foreign body reactions of PEEK, three main strategies were investigated: physical or chemical surface modification, preparation of functional PEEK composites by blending bioactive materials, and design of three-dimensional porous PEEK materials. The surface properties of biomaterials play a crucial role in cell / implant interactions and will ultimately affect the integration between implant and bone tissue during healing. Therefore, we propose a carbon fiber reinforced polyetheretherketone composite material, its preparation method, and its applications. Summary of the Invention
[0004] The purpose of this invention is to provide a method for preparing and applying bioactive carbon fiber reinforced composite materials, aiming to solve the problems mentioned in the background art.
[0005] To achieve the above objectives, the present invention provides the following technical solution:
[0006] A method for preparing a bioactive carbon fiber reinforced composite material includes the following steps:
[0007] Step S1: Design double-stranded DNA, with X strand being AATCCAATCCCAATCCCAATCCCAATCCC and Y strand being TTAGTGTTAGGTTTAGGGTTAGTG. The obtained DNA sequence is purified using HPLC.
[0008] Step S2: Take a carbon fiber reinforced polyether ether ketone composite material and pretreat it; place gold in a molybdenum evaporation boat of a vacuum thermal evaporator, and place the pretreated carbon fiber reinforced polyether ether ketone composite material in a sample tray above the evaporation boat. Use a molecular pump to remove the internal air; control the temperature by controlling the current of the evaporation boat, so that the gold melts and boils, and the gold vapor gradually condenses and forms a polycrystalline gold layer on the carbon fiber reinforced polyether ether ketone composite material, thus obtaining a carbon fiber reinforced polyether ether ketone composite material with a gold layer loaded.
[0009] Step S3: Immerse the gold-loaded carbon fiber reinforced polyether ether ketone composite material in a phosphate buffer solution containing X-strand DNA, incubate in a shaker at 37°C, and wash with deionized water; immerse the washed composite material in a phosphate buffer solution containing Y-strand DNA, incubate in a shaker at 37°C, and wash with deionized water to obtain the DNA-modified carbon fiber reinforced polyether ether ketone composite material.
[0010] Step S4: The DNA-modified carbon fiber reinforced polyether ether ketone composite material is immersed in a phosphate buffer solution of 6-mercapto-1-hexanol and incubated in a constant temperature shaker at 37°C. Then it is rinsed with deionized water and air-dried to obtain the DNA-loaded carbon fiber reinforced polyether ether ketone composite material.
[0011] Furthermore, the specific operation of step S1 is as follows:
[0012] Step S11: Design double-stranded DNA. The X strand is AATCCAATCCCAATCCCAATCCCAATCCC. To enhance the binding affinity of the DNA to the gold layer, a thiol group (C6SH) is modified at the 5' end. To facilitate the breakage of the double-stranded DNA into single strands, some base pairs are mismatched. The Y strand is TTAGTGTT.
[0013] The obtained DNA sequence was purified by HPLC to achieve an OD value of 1.6-1.8.
[0014] Furthermore, the specific operation of step S2 is as follows:
[0015] Step S21: The carbon fiber reinforced polyether ether ketone composite material is ultrasonically cleaned with acetone, ethanol and distilled water in sequence, and then vacuum dried to obtain the pretreated carbon fiber reinforced polyether ether ketone composite material.
[0016] Step S22: Place the gold in the molybdenum evaporation boat of the vacuum thermal evaporator, and place the pretreated carbon fiber reinforced polyetheretherketone composite material in the sample tray above the evaporation boat. Use a molecular pump to purge the internal air, which is then dispersed to 4 × 10⁻⁶. 4 -8×10 4 Pa;
[0017] Step S23: The temperature is controlled by adjusting the current of the evaporation boat, which is 10-30 mA, and the coating speed is maintained at 0.6-0.8 Ås. -1 The process involves melting and boiling the gold, causing the gold vapor to gradually condense and form a polycrystalline gold layer on the carbon fiber reinforced polyether ether ketone composite material, thus obtaining a carbon fiber reinforced polyether ether ketone composite material with a gold layer.
[0018] Furthermore, the specific operation of step S3 is as follows:
[0019] Step S31: Immerse the carbon fiber reinforced polyether ether ketone composite material loaded with gold layer into a phosphate buffer solution containing 3-5 mM X-strand DNA, incubate in a constant temperature shaker at 37°C for 1-5 h, and wash with deionized water.
[0020] Step S32: Immerse the cleaned composite material in a phosphate buffer solution containing 3-5 mM Y-strand DNA, incubate in a constant temperature shaker at 37°C for 1-5 h, and wash with deionized water to obtain DNA-modified carbon fiber reinforced polyether ether ketone composite material.
[0021] Furthermore, the specific operation of step S4 is as follows:
[0022] Step S41: The DNA-modified carbon fiber reinforced polyether ether ketone composite material is immersed in a 1-5 mM phosphate buffer solution of 6-mercapto-1-hexanol and incubated in a constant temperature shaker at 37°C for 1-5 h to remove the non-specific adsorption between the DNA and the gold layer. Then it is rinsed with deionized water and air-dried to obtain the DNA-loaded carbon fiber reinforced polyether ether ketone composite material.
[0023] A bioactive carbon fiber reinforced composite material prepared by the method described above.
[0024] Application of a bioactive carbon fiber reinforced composite material as described above in the preparation of bone graft materials, and / or bone fixation materials, and / or bone repair materials.
[0025] Compared with the prior art, the beneficial effects of the present invention are:
[0026] 1. The bioactive carbon fiber reinforced composite material obtained by this invention innovatively introduces DNA into medical bone repair materials. By responding to various external stimuli (pH, voltage), the DNA helical structure can be switched, thereby regulating surface properties such as surface wettability and zeta potential. It is an advanced material for bone engineering applications.
[0027] 2. The preparation method provided by this invention retains the elastic modulus of polyetheretherketone material consistent with that of human cortical bone, does not introduce elements that are toxic or harmful to the human body, and improves the biocompatibility of polyetheretherketone material. It is a well-designed material for bone engineering applications.
[0028] 3. The preparation method provided by this invention is low in cost, easy to operate, and does not require high-level instruments and equipment. It is an excellent method for improving the bioactivity of polyether ether ketone composite materials.
[0029] 4. The bioactive carbon fiber reinforced composite material prepared by this invention has excellent performance and reasonable structure, which can meet the requirements of most clinical applications such as bone grafting, bone fixation and bone repair, and can be used for bone grafting under load. Attached Figure Description
[0030] Figure 1 This is a schematic diagram of circular dichroism (CD) of DNA obtained in Example 1 of the present invention under different pH conditions.
[0031] Figure 2 This is a schematic diagram of the structural transformation of DNA obtained in Example 1 of the present invention under different pH conditions.
[0032] Figure 3 This is a schematic diagram of the zeta potential test of DNA obtained in Example 1 of the present invention under different pH conditions; wherein, (a) is a schematic diagram of the zeta potential test of DNA at pH=5, and (b) is a schematic diagram of the zeta potential test of DNA at pH=9.
[0033] Figure 4 This is a schematic diagram of the DNA-loaded carbon fiber reinforced polyether ether ketone composite material obtained in Example 1 of the present invention under different pH conditions using confocal laser (CLSM); wherein, (a) is CFRPEEK
[0034] (a) is a schematic diagram of CLSM of @DNA in a pH=5 environment, and (b) is a schematic diagram of CLSM of CFRPEEK@DNA in a pH=9 environment.
[0035] Figure 5This is a schematic diagram of Fourier transform attenuated total reflectance infrared spectroscopy (ATR-FTIR) of the DNA-loaded carbon fiber reinforced polyether ether ketone composite material obtained in Example 1 of this invention; wherein, 1 is a schematic diagram of ATR-FTIR of DNA on a silicon wafer; 2 is a schematic diagram of ATR-FTIR of CFRPEEK@Au reacting with 3 mM DNA (both X and Y chains are 3 mM) to obtain CFRPEEK@DNA; 3 is CFRPE
[0036] A schematic diagram of ATR-FTIR of CFRPEEK@DNA obtained by reacting EK@Au with 4mM DNA (4 mM for both X and Y strands); 4 is a schematic diagram of ATR-FTIR of CFRPEEK@DNA obtained by reacting CFRPEEK@Au with 5mM DNA (5 mM for both X and Y strands).
[0037] Figure 6 This is a schematic diagram of the contact angle test of the surface of the DNA-loaded carbon fiber reinforced polyether ether ketone composite material obtained in Example 1 of the present invention under different pH conditions.
[0038] Figure 7 This is a schematic diagram of the contact angle test of the surface of the DNA-loaded carbon fiber reinforced polyether ether ketone composite material obtained in Example 1 of the present invention under different voltage conditions.
[0039] Figure 8 This is a comparative diagram showing the results of apoptosis experiments on rBMSCs cells of the DNA-loaded carbon fiber reinforced polyether ether ketone composite material obtained in Example 1 of this invention; wherein, CFRPEEK@DNA-1 represents the apoptosis of the DNA-loaded carbon fiber reinforced polyether ether ketone composite material without current stimulation; CFRPEEK
[0040] @DNA-2 represents the apoptosis of DNA-loaded carbon fiber reinforced polyether ether ketone composite material under 1V voltage stimulation. Detailed Implementation
[0041] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0042] The specific implementation of the present invention will be described in detail below with reference to specific embodiments.
[0043] Example 1: A method for preparing a bioactive carbon fiber reinforced polyether ether ketone composite material according to an embodiment of the present invention includes the following steps:
[0044] S1. Design double-stranded DNA. The X strand is designed as AATCCAATCCCAATCCCAATCCCAATCCC (sequence listing as shown in SEQ ID NO:1). To enhance the binding ability of DNA to the gold layer, a thiol group (C6SH) is modified at the 5' end. To facilitate the breakage of double-stranded DNA into single strands, we choose to allow some base pairs to be mismatched. The Y strand is designed as TTAGTGTTAGGTTTAGGGTTAGTG (sequence listing as shown in SEQ ID NO:2). The obtained DNA sequence is purified by HPLC to make its OD value between 1.6 and 1.8.
[0045] S2. The carbon fiber reinforced polyether ether ketone (CFPEK) composite material was cut into circular pieces with a diameter of 9 mm and a thickness of 1.5 mm. These pieces were then ultrasonically cleaned three times (30 min each time) with distilled water, ethanol, and acetone, respectively. Afterward, they were dried in a vacuum drying oven at 60°C and stored for later use, yielding a pretreated CFPEK composite material (named CFRPEEK). The CFPEK composite material was then ultrasonically cleaned with acetone, ethanol, and distilled water, followed by vacuum drying, again yielding a pretreated CFPEK composite material. Gold was placed in a molybdenum evaporation boat within a vacuum thermal evaporator, and the pretreated CFPEK composite material was placed in a sample tray above the evaporation boat. Internal air was removed using a molecular pump, and the air inside the pump was dispersed to a density of 4 × 10⁻⁶. 4 -8×10 4 Pa; the temperature is controlled by adjusting the current in the evaporation boat, which is 10-30 mA, and the coating speed is maintained at 0.6-0.8 Ås. -1 The gold was melted and boiled, and the gold vapor gradually condensed and formed a polycrystalline gold layer on the sample, resulting in a carbon fiber reinforced polyether ether ketone composite material with a gold layer (named CFRPEEK@Au).
[0046] The aforementioned carbon fiber reinforced polyether ether ketone composite material is derived from the long carbon fiber reinforced polyether ether ketone prepared by the invention patent (application number 201710504295.X, invention name: long carbon fiber reinforced polyether ether ketone composite material and its preparation method), wherein the carbon fiber: polyether ether ketone = 30:70 (wt%).
[0047] The specific preparation steps are divided into two parts: the fabrication of three-dimensional (3D) needle-punched felt preforms and vacuum melt hot pressing. In the 3D needle-punched felt preform process, polyetheretherketone (PEEK) multifilaments are spun from spinning-grade PEEK material with a melt index of 42 g / 10 min using a high-temperature melt spinning machine (Beijing Shibuya Equipment Co., Ltd., China). The obtained PEEK fibers and carbon fibers (T700-24K, Toray, Japan) are cut into 40 mm pieces using a fiber cutter. Then, 70% PEEK fibers and 30% carbon fibers are washed, mixed, carded, laid, and needle-punched to prepare carbon fiber reinforced PEEK composite needle-punched felt preforms. In the vacuum melt hot pressing process, the carbon fiber reinforced PEEK needle-punched felt preforms are cut to mold size and then placed in a vacuum hot press. After a heating-pressing-saturation-cooling molding process, the carbon fiber reinforced PEEK composite material is finally obtained through demolding. The carbon fiber reinforced polyetheretherketone (PEEK) composite material has an elastic modulus of 18-20 GPa, which is consistent with the elastic modulus of human cortical bone. This will reduce the risk of osteoporosis and bone resorption caused by stress shielding due to elastic mismatch between the composite material and human bone after implantation. In addition, the carbon fiber reinforced PEEK is also isotropic.
[0048] S3. Take a carbon fiber reinforced polyether ether ketone composite material loaded with a gold layer, and immerse the carbon fiber reinforced polyether ether ketone composite material loaded with a gold layer in a phosphate buffer solution containing 3-5 mM X-chain DNA. Incubate in a constant temperature shaker at 37°C for 1-5 h, and wash with deionized water. Immerse the washed composite material in a phosphate buffer solution containing 3-5 mM Y-chain DNA, and incubate in a constant temperature shaker at 37°C for 1-5 h. Wash with deionized water to obtain a carbon fiber reinforced polyether ether ketone composite material with initial DNA modification.
[0049] S4. The DNA-modified carbon fiber reinforced polyether ether ketone composite material was immersed in 1-5 mM 6-mercapto-1-hexanol phosphate buffer solution and incubated in a constant temperature shaker at 37°C for 1-5 h to remove the non-specific adsorption between DNA and the gold layer. Then it was rinsed with deionized water and air-dried to obtain the DNA-loaded carbon fiber reinforced polyether ether ketone composite material (named CFRPEEK@DNA).
[0050] In this embodiment of the invention, the following experiment was conducted:
[0051] Experiment 1: The DNA obtained in Example 1 was subjected to CD spectrum analysis in phosphate buffer solutions at pH=5 and pH=9, respectively. The results are as follows: Figure 1 As shown, the peak wavelength of DNA was 281 nm in phosphate buffer at pH 5 and 275 nm in phosphate buffer at pH 9. This confirms that the conformational transition of double-stranded DNA can be triggered by changes in pH. Figure 2 As shown, under acidic conditions (pH=5), intramolecular atypical base pair interactions between protonated and unprotonated cytosine residues (i.e., C:C base pairs) on the X strand cross-link to form the i-motif conformation. This structure is defined as the closed form of DNA, in which the Y strand adopts a random coil conformation in solution. Conversely, at pH=9, the cytosine bases become deprotonated, so X unfolds in solution and hybridizes with the Y strand to form an extended double helix structure, i.e., the open form of DNA.
[0052] The DNA obtained in Example 1 was subjected to Zeta potential tests in phosphate buffer solutions at pH=5 and pH=9, respectively. The results are as follows: Figure 3 As shown, (a) is a schematic diagram of the zeta potential test of DNA at pH=5, and (b) is a schematic diagram of the zeta potential test of DNA at pH=9.
[0053] Figure 3 Zeta potential measurements showed that in the open mode of DNA, the extended double helix structure encapsulates the phosphate groups within the base pairs, resulting in a charge of -27.5 mV. This negative charge is inherent to double-stranded DNA. In the closed mode of DNA, intramolecular atypical base pair interactions between protonated and unprotonated cytosine residues (i.e., C:C base pairs) on the X strand cross-link to form the i-motif conformation. Although protonation introduces more positive charge, this also leads to a large number of phosphate groups being exposed on the DNA molecule surface, resulting in a greater negative surface charge of -33.6 mV. Sufficient negative surface charge in both the closed and open states is beneficial for early cell adhesion. The difference between these two states may influence cell adhesion, proliferation, and osteogenic differentiation, and provide a basis for the intelligentization of carbon fiber reinforced polyetheretherketone (PEEK) materials.
[0054] Experiment 2: The surface of the DNA-loaded carbon fiber reinforced polyetheretherketone composite material obtained in Example 1 was subjected to DAPI staining followed by laser confocal microscopy (CLSM) testing. The results are as follows: Figure 4 As shown, (a) is a schematic diagram of CLSM of CFRPEEK@DNA in a pH=5 environment, and (b) is a schematic diagram of CLSM of CFRPEEK@DNA in a pH=9 environment.
[0055] Depend on Figure 4As can be seen, dense DNA arrangement appears on the treated carbon fiber reinforced polyetheretherketone (PEEK) surface. The DNA on the PEEK surface does not lose its pH-sensitive properties and can reversibly switch from closed to open mode. When the ambient pH is 9, the closed mode switches to the open mode, and the DAPI dye embeds into the small groove between three consecutive AT base pairs, exhibiting blue fluorescence at an excitation wavelength of 488 nm.
[0056] The surface of the DNA-loaded carbon fiber reinforced polyetheretherketone composite material obtained in Example 1 was subjected to ATR-FTIR spectral analysis, and the results are as follows: Figure 5 As shown, 1 is a schematic diagram of ATR-FTIR of DNA on a silicon wafer; 2 is a schematic diagram of ATR-FTIR of CFRPEEK@Au reacting with 3 mM DNA (both X and Y chains are 3 mM) to obtain CFRPEEK@DNA; 3 is a schematic diagram of ATR-FTIR of CFRPEEK@Au reacting with 4 mM DNA (both X and Y chains are 4 mM) to obtain CFRPEEK@DNA; 4 is a schematic diagram of ATR-FTIR of CFRPEEK@Au reacting with 5 mM DNA (both X and Y chains are 5 mM) to obtain CFRPEEK@DNA.
[0057] Depend on Figure 5 It can be seen that the first point is at 1710 cm. -1 The nearby amide I peak is caused by the vibration of amide bonds in the DNA molecule, followed by the peak at 1630 cm⁻¹. -1 Nearby amide II peak; also at 1480 cm⁻¹ -1 The nearby thymine ring peak is produced by the vibration of the thymine group in the DNA molecule. Additionally, a phosphate backbone peak appears at 1080 cm⁻¹. -1 Nearby; at 2516 cm -1 This peak represents the stretching vibration of the Au-S bond. It demonstrates that DNA is covalently cross-linked to the surface of the carbon fiber reinforced polyetheretherketone composite material via Au-S, and that the higher the DNA concentration, the higher the Au-S covalent cross-linking density.
[0058] Experiment 3: The surface of the DNA-loaded carbon fiber reinforced polyetheretherketone composite material obtained in Example 1 was subjected to hydrophilicity tests under different pH and voltage conditions. The results are as follows: Figure 6 and Figure 7 As shown.
[0059] Depend on Figure 6It can be seen that the CFRPEEK@DNA obtained after the modification treatment in Example 1 exhibits the strongest hydrophilicity at pH=9, and the weakest hydrophilicity at pH=5, with a gradient change in hydrophilicity as the pH increases. Notably, CFRPEEK@DNA shows significant changes at pH=6 and pH=7, which is presumably because the critical value for the switch between on and off modes is reversible between pH=6 and pH=7.
[0060] Depend on Figure 7 It can be seen that the CFRPEEK@DNA obtained after the modification treatment in Example 1 exhibits the strongest hydrophilicity at a voltage of 0 V, while its hydrophilicity is weakest at a voltage of 4 V. Furthermore, the water contact angle increases gradually with increasing voltage. The change in contact angle of CFRPEEK@DNA with increasing voltage is almost linear, which is because the DNA pattern switching is sensitive to acid and alkaline reactions but exhibits a hysteresis in response to electrical stimulation.
[0061] Experiment 3: The cytotoxicity of the DNA-loaded carbon fiber reinforced polyether ether ketone composite material prepared by the above method was evaluated by in vitro culture experiment of rat bone marrow mesenchymal stem cells (rBMSCs).
[0062] Flow cytometry was used to detect cell apoptosis on the material surface; the specific procedure is as follows:
[0063] 1) Place the samples sterilized by 15K cobalt-60 irradiation into a 48-well culture plate, with a drop density of 1×10⁻⁶ per well. 4 cell / mL cell suspension;
[0064] 2) Place the cell culture plate in a cell culture incubator with 5% CO2 and saturated humidity at 37°C and change the culture medium every 2-3 days;
[0065] 3) After 3 days of cell culture, the Annexin V-PE apoptosis detection kit (Beyotime, China) was used to detect phosphatidylserine residues appearing on the cell membrane surface during apoptosis. Cells were treated with 0.25% trypsin / EDTA, centrifuged at 1000 rpm for 5 min, the supernatant was discarded, and the cells were collected. 50,000-100,000 cells were resuspended, centrifuged at 1000 g for 5 min, the supernatant was discarded, and 195 μl of Annexin V-PE binding buffer was added to gently resuspend the cells. 5 μl of Annexin V-PE was added and gently mixed. The cells were incubated at room temperature (20-25ºC) in the dark for 10-20 min, then placed on ice. Flow cytometry analysis was then performed immediately.
[0066] in, Figure 8This is a comparative diagram showing the results of apoptosis experiments on rBMSCs cells using the DNA-loaded carbon fiber reinforced polyether ether ketone composite material obtained in Example 1. CFRPEEK@DNA-1 represents the apoptosis of the DNA-loaded carbon fiber reinforced polyether ether ketone composite material without stimulation; CFRPEEK@DNA-2 represents the apoptosis of the DNA-loaded carbon fiber reinforced polyether ether ketone composite material stimulated with 1V.
[0067] Depend on Figure 8 It can be seen that the apoptosis of cells on the CFRPEEK@DNA-2 surface was significantly better than that in other groups, indicating a higher cell survival rate. This shows that the carbon fiber reinforced polyether ether ketone composite material loaded with DNA has good biological activity, which is the result of the combined effect of surface charge, hydrophilicity and surface energy of the material.
[0068] One embodiment of the present invention provides a bioactive carbon fiber reinforced polyether ether ketone composite material prepared by the preparation method described above.
[0069] One embodiment of the present invention provides the application of a bioactive carbon fiber reinforced polyether ether ketone composite material as described above in the preparation of bone graft materials, and / or bone fixation materials, and / or bone repair materials.
[0070] The above are merely preferred embodiments of the present invention. It should be noted that those skilled in the art can make several modifications and improvements without departing from the concept of the present invention, and these should also be considered within the scope of protection of the present invention. These modifications and improvements will not affect the effectiveness of the implementation of the present invention or the practicality of the patent.
Claims
1. A method for preparing a bioactive carbon fiber reinforced composite material, characterized in that, Includes the following steps: Step S1: Design double-stranded DNA, with the X strand being AATCCAATCCCAATCCCAATCCCAATCCC. Modify the 5' end with a thiol group and allow some base pairs to mismatch with the Y strand, resulting in the Y strand being TTAGTGTTAGGTTTAGGGTTAGTG. Purify the obtained DNA sequence using HPLC to ensure that the OD value of the DNA sequence is between 1.6 and 1.
8. Step S2: Take a carbon fiber reinforced polyether ether ketone composite material and pretreat it; place gold in a molybdenum evaporation boat of a vacuum thermal evaporator, and place the pretreated carbon fiber reinforced polyether ether ketone composite material in a sample tray above the evaporation boat. Use a molecular pump to remove the internal air; control the temperature by controlling the current of the evaporation boat, so that the gold melts and boils, and the gold vapor gradually condenses and forms a polycrystalline gold layer on the carbon fiber reinforced polyether ether ketone composite material, thus obtaining a carbon fiber reinforced polyether ether ketone composite material with a gold layer loaded. Step S3: Immerse the gold-loaded carbon fiber reinforced polyether ether ketone composite material in a phosphate buffer solution containing X-strand DNA, incubate in a shaker at 37°C, and wash with deionized water; immerse the washed composite material in a phosphate buffer solution containing Y-strand DNA, incubate in a shaker at 37°C, and wash with deionized water to obtain the DNA-modified carbon fiber reinforced polyether ether ketone composite material. Step S4: The DNA-modified carbon fiber reinforced polyether ether ketone composite material is immersed in a phosphate buffer solution of 6-mercapto-1-hexanol and incubated in a constant temperature shaker at 37°C. Then it is rinsed with deionized water and air-dried to obtain the DNA-loaded carbon fiber reinforced polyether ether ketone composite material.
2. The method for preparing bioactive carbon fiber reinforced composite material according to claim 1, characterized in that, The specific operation of step S2 is as follows: Step S21: The carbon fiber reinforced polyether ether ketone composite material is ultrasonically cleaned with acetone, ethanol and distilled water in sequence, and then vacuum dried to obtain the pretreated carbon fiber reinforced polyether ether ketone composite material. Step S22: Place the gold in the molybdenum evaporation boat of the vacuum thermal evaporator, and place the pretreated carbon fiber reinforced polyetheretherketone composite material in the sample tray above the evaporation boat. Use a molecular pump to purge the internal air, which is then dispersed to 4 × 10⁻⁶. 4 -8×10 4 Pa; Step S23: The temperature is controlled by adjusting the current of the evaporation boat, which is 10-30 mA, and the coating speed is maintained at 0.6-0.8 Ås. -1 The process involves melting and boiling the gold, causing the gold vapor to gradually condense and form a polycrystalline gold layer on the carbon fiber reinforced polyether ether ketone composite material, thus obtaining a carbon fiber reinforced polyether ether ketone composite material with a gold layer.
3. The method for preparing bioactive carbon fiber reinforced composite material according to claim 1, characterized in that, The specific operation of step S3 is as follows: Step S31: Immerse the carbon fiber reinforced polyether ether ketone composite material loaded with gold layer into a phosphate buffer solution containing 3-5 mM X-strand DNA, incubate in a constant temperature shaker at 37°C for 1-5 h, and wash with deionized water. Step S32: Immerse the cleaned composite material in a phosphate buffer solution containing 3-5 mM Y-strand DNA, incubate in a constant temperature shaker at 37°C for 1-5 h, and wash with deionized water to obtain DNA-modified carbon fiber reinforced polyether ether ketone composite material.
4. The method for preparing bioactive carbon fiber reinforced composite material according to claim 1, characterized in that, The specific operation of step S4 is as follows: Step S41: The DNA-modified carbon fiber reinforced polyether ether ketone composite material is immersed in a 1-5 mM phosphate buffer solution of 6-mercapto-1-hexanol and incubated in a constant temperature shaker at 37°C for 1-5 h to remove the non-specific adsorption between the DNA and the gold layer. Then it is rinsed with deionized water and air-dried to obtain the DNA-loaded carbon fiber reinforced polyether ether ketone composite material.
5. A bioactive carbon fiber reinforced composite material prepared by any one of the preparation methods according to claims 1-4.
6. The use of the bioactive carbon fiber reinforced composite material according to claim 5 in the preparation of bone graft materials, and / or bone fixation materials, and / or bone repair materials.
Citation Information
Patent Citations
Carbon fiber long fiber reinforced polyether ether ketone-based composite materials and their preparation methods
CN107245810B
Kit and detection method for selectively detecting concentration of Pb ions and Ag ions
CN109100339A
Novel DNA hydrogel and preparation method thereof
CN111848981A